Afirmasi Positif Dalam Meningkatkan Self Efficacy Di MA al-Qur’an La Raiba Hanifida Bandung Diwek Jombang - Zuha el Widad; Khoirotul Idawati (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2023)
Acceleration in the world of education is needed to keep pace with the unstoppable acceleration of world development, not a few people call for success starting from belief, but they are surprised by the success of others and tend to be unsure of themselves/not sure they can. Therefore, it is necessary to have self-confidence in success (self-efficacy) which is raised through positive affirmations. This study uses a qualitative approach with a case study type of research. Data collection techniques using observation, interviews, and communication studies. The application of positive affirmations at Madrasah Aliyah al-Qur'an La Raiba Hanifida consists of 3 categories, namely the slogan and jargon “Future Leaders, Creators of Civilization”, positive affirmations in the form of spiritual activities and reading 3 Greetings of Commitment. Obstacles that arise come from internal (belief system rejection)